Mechanical Ventilation–induced Diaphragm Atrophy Strongly Impacts Clinical Outcomes - Goligher, Ewan C.; Dres, Martin; Fan, Eddy; Rubenfeld, Gordon D.; Scales, Damon C.; Herridge, Margaret S.; Vorona, Stefannie; Sklar, Michael C.; Rittayamai, Nuttapol; Lanys, Ashley; Murray, Alistair; Brace, Deborah; et al. (American journal of respiratory and critical care medicine, 2018)
Diaphragm dysfunction worsens outcomes in mechanically ventilated patients, but the clinical impact of potentially preventable changes in diaphragm structure and function caused by mechanical ventilation is unknown. To determine whether diaphragm atrophy developing during mechanical ventilation leads to prolonged ventilation. Diaphragm thickness was measured daily by ultrasound in adults requiring invasive mechanical ventilation; inspiratory effort was assessed by thickening fraction. The primary outcome was time to liberation from ventilation. Secondary outcomes included complications (reintubation, tracheostomy, prolonged ventilation, or death). Associations were adjusted for age, severity of illness, sepsis, sedation, neuromuscular blockade, and comorbidity. Of 211 patients enrolled, 191 had two or more diaphragm thickness measurements. Thickness decreased more than 10% in 78 patients (41%) by median Day 4 (interquartile range, 3-5). Development of decreased thickness was associated with a lower daily probability of liberation from ventilation (adjusted hazard ratio, 0.69; 95% confidence interval [CI], 0.54-0.87; per 10% decrease), prolonged ICU admission (adjusted duration ratio, 1.71; 95% CI, 1.29-2.27), and a higher risk of complications (adjusted odds ratio, 3.00; 95% CI, 1.34-6.72). Development of increased thickness (n = 47; 24%) also predicted prolonged ventilation (adjusted duration ratio, 1.38; 95% CI, 1.00-1.90). Decreasing thickness was related to abnormally low inspiratory effort; increasing thickness was related to excessive effort. Patients with thickening fraction between 15% and 30% (similar to breathing at rest) during the first 3 days had the shortest duration of ventilation. Diaphragm atrophy developing during mechanical ventilation strongly impacts clinical outcomes. Targeting an inspiratory effort level similar to that of healthy subjects at rest might accelerate liberation from ventilation.